Development of the component base of unified assenbly and parts of installation clamping devices - Yakovenko, Ihor Eduardovich; Permyakov, Alexandr Anatolievich; Kharchenko, Oleksandr Sergvyovich (Національний технічний університет "Харківський політехнічний інститут", 2022)
The issues of unification of units and elements of special equipment were further developed in the work. Issues of a theoretical approach to the creation of an element base of unified assemblies and parts for existing layout schemes for mounting and clamping devices of equipment built on the principles of aggregation are considered. in order to subsequently minimize the cost of design and production. The authors propose a two-stage methodology for unifying fixture elements in order to create a reference and regulatory framework for such elements. At the first stage, based on the analysis of the functional purpose of the structural elements of various layout schemes of devices, a list of parts is established, the unification of which is possible and expedient. At the second stage, based on the strength analysis of the selected elements and the analysis of statistical information on the geometric parameters of the installed workpieces for various layout schemes of fixtures, the number of standard sizes and geometric parameters of these parts are determined. This approach allows you to create a constantly updated and edited database of unified fixture elements, which can be used in the process of computer-aided design.

У роботі отримали подальший розвиток питання уніфікації вузлів та елементів спеціального обладнання. Розглянуто питання теоретичного підходу до створення елементної бази уніфікованих вузлів та деталей для існуючих компонувальних схем настановно затискних пристроїв обладнання, побудованого на принципах агрегатування з метою подальшої мінімізації витрат на проектування та виробництво. Авторами пропонується двоетапна методика проведення уніфікації елементів пристроїв з метою створення довідково-нормативної бази таких елементів. На першому етапі на підставі аналізу функціонального призначення структурних елементів різних компоновочних схем пристроїв встановлюється перелік деталей, уніфікація яких можлива та доцільна. На другому етапі на підставі аналізу міцності обраних елементів і аналізу статистичної інформації за геометричними параметрами встановлюваних заготовок для різних компоновочних схем пристосувань встановлюється кількість типорозмірів і геометричні параметри цих деталей. Такий підхід дозволяє створити постійно поповнювану та редаговану базу уніфікованих елементів пристроїв, яка може бути використана у процесі автоматизованого проектування.
Розробка елементної бази уніфікованих вузлов і деталей установково затискових використань
Keywords: aggregated equipment; mounting fixture; unification; layout; strength analysis; elements; standard size; агрегатоване обладнання; установочно-затискний пристрій; уніфікація; компоновка; аналіз міцності; елементи; типорозмір